Absence of Genotoxic and Mutagenic Effects of Zingiber zerumbet (L.) Smith (Zingiberaceae) Extract. (15th July 2012) - Chang, Chia Ju; Tzeng, Thing-Fong; Liou, Shorong-Shii; Chang, Yuan-Shiun; Liu, I-Min
Abstract : The present study evaluated the potential genotoxicity of the ethanol extracts from the rhizome of Zingiber zerumbet (L.) Smith (EEZZR) using a standard battery of tests. Chemical analysis with liquid chromatography-tandem mass spectrometry revealed that EEZZR contained Zerumbone (200.3 ± 0.37  μg/g) and 6-gingerol (102.5 ± 0.28  μg/g). There were no increases in the number of revertant colonies with EEZZR at concentrations of 150–5000 μg per plate, regardless of the metabolic activation system (S-9 mix) used in the histidine-dependent auxotrophic mutants of Salmonella typhimurium (strains TA97, TA98, TA100, TA102, and TA1535) compared to the vehicle control. Furthermore, EEZZR at doses of 150–5000 μg mL -1 did not increase the number of structural aberrations in Chinese hamster lung cells in the presence or absence of S-9 mix. An oral administration of EEZZR to ICR mice, with doses of up to 2000 mg/kg, caused no significant increases in the number of micronucleated polychromatic erythrocytes (MNPCEs) and mean ratio of polychromatic erythrocytes to total erythrocytes. Lastly, RZZEE did not increase the incidence of MNPCEs in bone marrow. Based on these findings, it may be concluded that the use of EEZZR in traditional medicine poses no risk of genotoxicity.